Community Structure and Function of Epiphytic Bacteria Associated With Myriophyllum spicatum in Baiyangdian Lake, China - Sun, Lei; Wang, Jiashuo; Wu, Yangyang; Gao, Tianyu; Liu, Cunqi (Frontiers in Microbiology, 2021)
Epiphytic bacteria on the surfaces of submerged macrophytes play important roles in the growth of the host plant, nutrient cycling and the conversion of pollutants in aquatic systems. A knowledge of the epiphytic bacterial community structure could help us to understand these roles. In this study, the abundance, diversity and functions of the epiphytic bacterial community of Myriophyllum spicatum collected from Baiyangdian Lake in June, August and October of 2019 were studied using quantitative PCR (qPCR), high-throughput sequencing and the prediction of functions. An analysis using qPCR showed that the epiphytic bacteria were the most abundant in October and the least abundant in August. High-throughput sequencing revealed that Proteobacteria, Gammaproteobacteria, and Aeromonas were the dominant phylum, class, and genus in all of the samples. The common analyses of OTUs, NMDS and LDA showed that the epiphytic bacterial communities were clustered together based on the seasons. The results of a canonical correlation analysis showed that the key water quality index that affected the changes of epiphytic bacterial community of M. spicatum was the total phosphorus (TP). The changes in abundance of Gammaproteobacteria negatively correlated with the TP. Predictive results from FAPROTAX showed that the predominant biogeochemical cycle functions of the epiphytic bacterial community were chemoheterotrophy, nitrate reduction and fermentation. These results suggest that the epiphytic bacterial community of M. spicatum from Baiyangdian Lake varies substantially with the seasons and environmental conditions.